Study of fracture shaft of Femur and its outcome treated with K- Nail in Manipal Teaching Hospital - Sapkota, Krishna; Ranjeet, Niraj; Onta, Pratyenta Raj; Thapa, Pabin; Thapa, Upendra Jung (Asian Journal of Medical Sciences, 2018)
Background: Intramedullary interlocking nail is commonly accepted standard treatment in fracture shaft of femur. Its cost, technique, necessity of fracture table and image intensifier make it difficult in using for such cases where facilities are not available. In developing countries like Nepal open Kuntscher nailing is still an option for treating fracture shaft of femur. Its results and outcomes are comparable to that of intramedullary interlocking nails. Aims and Objectives: This study was undertaken to evaluate the outcome of Kuntscher nailing in fracture shaft of femur with regards to operative duration, union, infection, limb-length, and range of motion of knee and hip joints. Materials and Methods: This retrospective study included seventy-six patients with fracture shaft of femur. This study was conducted for a period from December 2014 to December 2017. The study outcome was assessed in terms of operative time duration, union, infection, limb-length, and range of motion of knee and hip joints. Results: Seventy six patients with fracture shaft of femur with mean age of 32.36 years ranging from 15 to 65 years were included in the study. Operation duration ranges from 55 to 95 minutes, with average healing time of 17 weeks. Wound infection was seen in 5% cases, with not much limb length discrepancy and knee range of motion 100 -135 degree achieved by the end of 9 months in more than 95 % cases. Conclusion: Kuntscher nail is still a relevant option for treatment of fracture shaft of femur with good functional and clinical outcome. Asian Journal of Medical Sciences Vol.9(6) 2018 90-92